2022
DOI: 10.3390/plants11212905
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Disease Resistance Parents and Genome-Wide Association Mapping of Resistance in Spring Wheat

Abstract: The likelihood of success in developing modern cultivars depend on multiple factors, including the identification of suitable parents to initiate new crosses, and characterizations of genomic regions associated with target traits. The objectives of the present study were to (a) determine the best economic weights of four major wheat diseases (leaf spot, common bunt, leaf rust, and stripe rust) and grain yield for multi-trait restrictive linear phenotypic selection index (RLPSI), (b) select the top 10% cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Several studies reported genes ( Bt4 , Bt5 , and Bt6 ) and QTLs associated with Cbt resistance on chromosome 1B (Dumalasová et al., 2012; Ehn et al., 2022; Fofana et al., 2008; Iqbal et al., 2022; Mourad et al., 2018; Muellner et al., 2021; Scmidt et al., 1969; Singh et al., 2016; Wang et al., 2009), 2B (Chen et al., 2016; Ehn et al., 2022; Iqbal et al., 2022; Steffan et al., 2022), and 6D (Gordon et al., 2020; Iqbal et al., 2022; Singh et al., 2016). The positions of the Cbt resistance genes and QTLs on 1B varied across populations and includes 11.2 Mb near BS00032266_51 in a diversity panel of bread wheat accessions from the USDA National Small Grains Collection (Ehn et al., 2022), 4.4–38.9 Mb in two RIL populations derived from Blizzard/Rainer and Bonneville/Rainer (Muellner et al., 2021), and 645.2 Mb in Canadian spring wheat (Iqbal et al., 2022). The physical position of the QCbt.dms‐1B identified in the present study, therefore, overlapped with the QTLs reported in the USDA bread wheat accessions and the two RIL (Blizzard/Rainer and Bonneville/ Rainer) populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported genes ( Bt4 , Bt5 , and Bt6 ) and QTLs associated with Cbt resistance on chromosome 1B (Dumalasová et al., 2012; Ehn et al., 2022; Fofana et al., 2008; Iqbal et al., 2022; Mourad et al., 2018; Muellner et al., 2021; Scmidt et al., 1969; Singh et al., 2016; Wang et al., 2009), 2B (Chen et al., 2016; Ehn et al., 2022; Iqbal et al., 2022; Steffan et al., 2022), and 6D (Gordon et al., 2020; Iqbal et al., 2022; Singh et al., 2016). The positions of the Cbt resistance genes and QTLs on 1B varied across populations and includes 11.2 Mb near BS00032266_51 in a diversity panel of bread wheat accessions from the USDA National Small Grains Collection (Ehn et al., 2022), 4.4–38.9 Mb in two RIL populations derived from Blizzard/Rainer and Bonneville/Rainer (Muellner et al., 2021), and 645.2 Mb in Canadian spring wheat (Iqbal et al., 2022). The physical position of the QCbt.dms‐1B identified in the present study, therefore, overlapped with the QTLs reported in the USDA bread wheat accessions and the two RIL (Blizzard/Rainer and Bonneville/ Rainer) populations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Iqbal et al. (2022) reported a Cbt resistance QTL at 7.4 Mb near D_contig17056_55 on chromosome 6D which accounted for 16.9% of the Cbt severity in Canadian spring wheat. Both Bt9 and Bt10 have been reported on the long and short arms of chromosome 6D, respectively (Menzies et al., 2006; Steffan et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A diversity panel of 196 spring wheat genotypes was phenotyped for the leaf rust resistance in the field. A GWAS approach using 90K SNP array revealed significant association of multiple SNPs on chromosomes 2B (QLr.dms-2B.2) and 2D (QLr.dms-2D) [90]. An AS gene LrNJ97 was identified from a Chines wheat line "Neijiang 977671" and linked with SSR markers on chromosome 2BL [91].…”
Section: Lr/qlr On Chromosome 2bmentioning
confidence: 99%